1986
DOI: 10.1177/34.2.2418101
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Plasmodium falciparum growth in culture using acridine orange and flow cytometry.

Abstract: The growth of Plasmodium falciparum in cultures of human red blood cells was studied using acridine orange to stain RNA and DNA, followed by flow cytometric analysis. The cyde of the parasite is characterized by a period of growth, prior to initiation ofDNA synthesis, in which a significant increase in red fluorescence is observed, with only a small change in green fluorescence. Following this phase, which is formally similar to the Gi period in mammalian

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…However, they require flow cytometers equipped with ultraviolet lasers that are not available in most laboratories. Nonspecific DNA staining agents, such as thiazole orange (7), acridine orange (8)(9)(10), ethidium bromide (11), propidium iodide (12), or hydroethidine (13)(14)(15), have also been used to stain nucleic acids from infected erythrocytes. Recently, YOYO-1, a cyanine dimer, has been added to this list (16).…”
mentioning
confidence: 99%
“…However, they require flow cytometers equipped with ultraviolet lasers that are not available in most laboratories. Nonspecific DNA staining agents, such as thiazole orange (7), acridine orange (8)(9)(10), ethidium bromide (11), propidium iodide (12), or hydroethidine (13)(14)(15), have also been used to stain nucleic acids from infected erythrocytes. Recently, YOYO-1, a cyanine dimer, has been added to this list (16).…”
mentioning
confidence: 99%
“…The labelling of parasitized RBCs (PRBC) was performed in the dark without permeabilization of the cells in two steps [10,13,31], using two nucleic acids staining: i) vital dye hydroethidine (HE) (Interchim 17084), which is metabolized into ethidium by esterases in intact PRBC (ethidium labelling of nucleic acids results in a red fluorescence emission) [11] (Figure 1B); and, ii) thiazole orange (TO) (Sigma 17237), which binding both to RNA and DNA emitting a green fluorescence [15]. HE is prepared at 10 mg/ml in dimethyl sulphoxide then stored at −20°C.…”
Section: Methodsmentioning
confidence: 99%
“…To counteract these difficulties, several dyes have been used to measure division of the nucleus by fluorimetry [8] or by flow cytometry. The most often used are: Hoechst 33258 [9], acridine orange [8,10,11], thiazole orange [12], hydroethidine [13], and recently YOYO-1 [5,14-16]. Sybergreen I based test was also standardized and is currently used in several laboratories [7].…”
Section: Introductionmentioning
confidence: 99%
“…Assess ment of RNA content in archival material is more difficult, however, and previous stud ies have noted a number of artifacts [18]. We and others [19][20][21] have shown that acridine orange selectively stains RNA in formalinfixed cells. Intrasample and daily variability in nuclear RNA measurements were within experimental error.…”
Section: Dnamentioning
confidence: 99%